A Women's Empowerment Model In Mangrove Forest Management In Tapak Kuda Village, Tanjung Pura District, Langkat District - Aulia, Farid; Savitri, Nita (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This research examines the model of empowering women in managing mangrove forests in Tapak Kuda Village, Tanjung Pura Regency, Langkat Regency as sustainable managers of mangrove forests. The existing conditions that have occurred so far show the inability of the government and stakeholders to synergize through mangrove forest management programs that involve local community participation in a sustainable, synergistic and systemic manner, so that implementation often experiences overlap. This multi-stakeholder uncertainty can be minimized if it is based on a model of empowering women in communities living around mangrove forests and stakeholder involvement in mangrove forest management that has been carried out, so that this research can become a reference for the government and stakeholders in systemic and sustainable mangrove forest management. The objectives of this research are: to determine the form of women's involvement as mangrove forest managers, to analyze the obstacles faced in efforts to empower women, to design a model for empowering women in sustainable mangrove forest management. Research Method uses a qualitative approach with descriptive analysis techniques to analyze the form of women's involvement in mangrove management, analyze the obstacles faced by women in managing mangrove forests, and design a model for women's empowerment in managing mangrove forests in a sustainable manner. Targeted outcomes in this research: 1. Women's Empowerment Model in Mangrove Forest Management in Tapak Kuda Village, Tanjung Pura District, Langkat Regency, 2. International Journal of Research and Review. Meanwhile, additional outputs targeted: 1. Accredited National Journal Sinta-3 Perspective. TKT proposed in this research: 4